OLIGARCHY AND DYNASTIC POLITICS IN INDONESIA - Jerry Indrawan; Putrawan Yuliandri; Hartanto Hartanto (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
Democracy gives everyone the freedom to choose and be chosen in elections. However, democracy also does not prohibit someone who has a family relationship with a public official from being elected in the election. This discourse gives birth to what is called oligarchy or dynasty in political life, especially in Indonesia. In this country, oligarchic politics and dynasty politics thrive along with the rapid development of its democratic life. Oligarchy and dynasty politics on the one hand are opposed by civil society, but on the other hand, candidates for public officials who are related to the incumbent are still elected by the people. That is why the debate about oligarchy and politics in Indonesia is very interesting to be used as a study. The purpose of this study is to analyze the idea of ​​the development of oligarchy and dynasty politics in a democratic medium, such as in Indonesia. The main finding in this study concludes two things, which are changes to the electoral system and revamping the political and campaign financing system. This study uses a descriptive qualitative method based on Winters' oligarchy theory.